Design and Development of Lasto Virtual Queue Management System - Basgaran, Priya Sri; IBRAHIM, NORAINI (Applied Information Technology And Computer Science, 2023)
Lasto Virtual Queue Management System (VQMS) is a web-based system that will assist the Lasto Computer Service Centre. This system is designed to regulate the queues of customers efficiently and effectively. This approach is required because controlling queues has been a big challenge at Lasto Computer Service Centre as the organization tends to become quite busy, particularly during peak periods. Activities in the prototyping model are used to develop Lasto VQMS. Apart from that, Lasto VQMS is written using PHP, HTML, CSS, JavaScript, the Bootstrap framework, and XAMPP server software. Whereas the database of the system will be developed using MySQL. This system is expected to efficiently manage customers and make their journey as pleasant and stress-free as possible by enhancing queueing processes by enabling customers to get their token virtually by scanning the QR code or by entering their email address. Additionally, the system will send an email notification when they are next in the line. The system passed 23 out of 23 test cases, equivalent to 100% of test cases. To conclude, this system is helpful in improving customer satisfaction and operational efficiency of the Lasto Computer Service Centre.